Реформа Российской академии наук: уроки для Украины - Батурин, Ю.М. (Наука та наукознавство, 2014)
Выступление заместителя президента РАН, директора Института истории науки и техники им. С.И. Вавилова РАН, члена-корреспондента РАН, Героя России Ю.М. Батурина на расширенном заседании Ученого совета ЦИПИН им. Г.М. Доброва НАН Украины 2 декабря 2013 года The article reproduces the author’s reflections and concerns about the reform in the Russian Academy of Sciences (RUS) and its implications for the RUS and lessons to be learnt by Ukraine. The author contemplates on what would be necessary to do in Ukraine to avoid the suddenness or weakness of a similar reform. What is required first of all is setting order within the domestic science system, at the level of research institutes. Also, a reform like this should by no means be a matter beyond the public opinion; the later should be prepared to it properly and in advance, so that the public could not be taken aback. It is very important to keep an eye on the early signs of reform, to secure a quick response on it. This would require contacts with persons from within the Academy of Sciences and with mass media, in order to disseminate the needed information at one’s request and to have quick access to information related to reform, requested by one. Another important point is setting up horizontal links and self-organization of research staff, in order to counteract arbitrary political decisions. It is important to launch, in due time, a debate on draft legal documents on a reform, to have one’s own elaborated strategy, which can be transformed, in case of need, into a legal rule with support from invited professional lawyers. Also, documenting of any meeting with officials concerning reform is important. The issues concerning Academy’s assets must be on top of the reform agenda.